2013
DOI: 10.1021/cm3038747
|View full text |Cite
|
Sign up to set email alerts
|

Spinel Metal Oxide-Alkali Carbonate-Based, Low-Temperature Thermochemical Cycles for Water Splitting and CO2 Reduction

Abstract: A manganese oxide-based, thermochemical cycle for water splitting below 1000 °C has recently been reported. The cycle involves the shuttling of Na+ into and out of manganese oxides via the consumption and formation of sodium carbonate, respectively. Here, we explore the combinations of three spinel metal oxides and three alkali carbonates in thermochemical cycles for water splitting and CO2 reduction. Hydrogen evolution and CO2 reduction reactions of metal oxides with a given alkali carbonate occur in the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Bayón et al demonstrated that the surface area of Mn 3 O 4 is the main factor, while the crystalline domain size has a secondary influence [16]. Xu et al [17] performed the multistep reactions on 200 mg Mn 3 O 4 /Na 2 CO 3 below 850 • C and demonstrated that the rates of H 2 releasing and Na + extraction depend on the redox properties of metals in ferrite-based oxides and the facility of intercalating alkali cations. Bayón et al [14] also studied the feasibility of the MnO/Na 2 CO 3 cycle, with a maximum conversion of 47% and a productivity of 20.1 µmol H 2 min −1 g −1 .…”
Section: Hydrogen Production By Water Splitting In Thermal Redox Systemsmentioning
confidence: 99%
“…Bayón et al demonstrated that the surface area of Mn 3 O 4 is the main factor, while the crystalline domain size has a secondary influence [16]. Xu et al [17] performed the multistep reactions on 200 mg Mn 3 O 4 /Na 2 CO 3 below 850 • C and demonstrated that the rates of H 2 releasing and Na + extraction depend on the redox properties of metals in ferrite-based oxides and the facility of intercalating alkali cations. Bayón et al [14] also studied the feasibility of the MnO/Na 2 CO 3 cycle, with a maximum conversion of 47% and a productivity of 20.1 µmol H 2 min −1 g −1 .…”
Section: Hydrogen Production By Water Splitting In Thermal Redox Systemsmentioning
confidence: 99%
“…Their drawbacks are mainly related to the potentially lower efficiency of the process, but lower operating temperatures may be achieved compared to those usually required by two-step processes. In addition to the older three-step sulfur-iodine cycle [104], Mn-oxide based three-step cycles have been more recently proposed [62,105,106]. The use of nanoparticles was also found to have a beneficial effect on lowering the maximum temperature of the cycle [107].…”
Section: Reactor/receivers For Water-splitting Redox Cyclesmentioning
confidence: 99%
“…There may be several reasons for these differences. (1) The entropy model may be inappropriate when both Fe 2+ and Fe 3+ are present because of rapid electron hopping between Fe 2+ and Fe 3+ , leading to local electronic entropy rather than a configurational term from positional disorder. The communal entropy arising from electron hopping between Fe 2+ and Fe 3+ may be destroyed in the solid solution by the addition of cobalt/ manganese and the oxidation of Fe 2+ to Fe 3+ .…”
Section: Entropies and Gibbs Free Energies Of Mixingmentioning
confidence: 99%
“…Spinels of iron, cobalt and manganese (Co 3 O 4 , Fe 3 O 4 , Mn 3 O 4 ) and their solid solutions are a subject of extensive research because of their applications in electrochemistry, catalysis, fuel cells, water splitting and other fields. 1,2 Fe 3 O 4 has an inverse spinel structure Fe 3+ [Fe 2+ Fe 3+ ]O 4 , with one Fe 3+ per formula unit on tetrahedral sites and the remaining Fe 2+ and Fe 3+ randomly distributed on octahedral sites. 3 Mn 3 O 4 and Co 3 O 4 are normal spinels, M 2+ [M 3+ M 3+ ]O 4 with M 2+ in tetrahedral sites and M 3+ in octahedral sites and their extent of disorder is expected to remain small at higher temperatures due to the large octahedral site preference of M 3+ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation